Morphological alterations of the reticular thalamic nucleus in Engrailed‐2 knockout mice - Pirone, Andrea (J Anat, 2020)
The reticular thalamic nucleus (Rt) is a sheet of neurons that surrounds the dorsal thalamus laterally, along its dorso‐ventral and rostro‐caudal axes. It consists of inhibitory neurons releasing gamma‐aminobutyric acid (GABA). This nucleus participates in the circuitry between the thalamus and the cerebral cortex, and its impairment is associated with neuro‐psychiatric disorders. In this study, we investigated the Rt anatomy of Engrailed‐2 knockout mice (En2(−/−)), a mouse model of autism spectrum disorder (ASD), using parvalbumin as an immunohistochemical marker. We compared 4‐ and 6‐week‐old wild type (WT) and En2(−/−) mice using various morphometric parameters: cell area, shape factor, circularity and cell density. Significant differences were present in 6‐week‐old male mice with different genetic background (WT vs. En2(−/−)): the Rt neurons of En2 (−/−) mice showed a bigger cell area, shape factor and circularity when compared with WT. Age (4 weeks vs. 6 weeks) influenced the shape factor of WT females, the circularity and cell density of En2 (−/−) males, and the shape factor and circularity of En2 (−/−) females. Gender affected cell density in 4‐week‐old WT mice, shape factor and cellularity of 6‐week‐old WT mice, and cell area, shape factor and cell density of En2 (−/−) at 6 weeks. Intrasubject (left–right) asymmetry of Rt was never observed. These results show for the first time that sex‐ and age‐related changes occur in the Rt GABAergic neurons of the En2 (−/−) ASD mouse model.